ROLE OF PRAKRITI IN SELECTION OF COSMETIC PRODUCTS - Suwarna V, *Umarkar; Deepak M, Vyas; Pragati P, Waghmare (International Journal of Ayurveda and Pharma Research, 2017)
Ayurveda is an ancient science of life. It attributes primary aim towards prevention and health maintenance. Health promotion depends on toxin (Ama) free systems, restoration of cellular nutrition and maintenance of balance of Doshas. The major preventive approaches for maintaining and improving the quality of life includes individualized specific daily regimen (Dinacharya), seasonal regimen (Rutucharya), behavioral and ethical consideration (Sadvrittas). Healthy lifestyle is emphasized as the determinant of longevity of life which depends on the Prakriti (bio-identity i.e. body - mind constitution) of an individual. Prakriti is an important concept of Ayurveda. Prakriti is a combination of Physical, Physiological and Psychological characteristics of an individual. In Ayurveda concept of personality and beauty is expressed in terms of Prakriti, Sara and Anguli Praman etc. Variation in skin characteristics are also mentioned in Ayurveda as per dominant Deha Prakriti. Day by day cosmetic field is gaining wide importance along with its increased demand. On other hand skin problems are also increasing which causes damage to skin due to overuse or misuse of cosmetics. It requires knowledge of cosmetic science along with Prakriti while choosing any cosmetics otherwise random use of any cosmetics may cause adverse effect on skin. Awareness about Prakriti gives guideline by suggesting Aahar vihar and lifestyle modification according to Prakriti so that one can maintain skin health. The main aim of this study is to provide awareness to healthy individuals about role of Prakriti while selecting skin care cosmetics products. For this study literature collection is done from various Samhita Granths, cosmetic books, thesis research work of related topics, and current research papers.